Bowel habits of exclusively breastfed 0-4 month-old babies - Edi S Tehuteru; Agus Firmansyah; Bambang Madiyono (Indonesian Pediatric Society, 2004)
Background Exclusively breastfed newborns have frequent bowelmovements and sometimes watery stool, which parents or doctorsmight think as diarrhea.Objective The aim of this study was to observe the bowel habitsof exclusively breastfed infants.Methods A longitudinal study was done on 100 babies born be-tween November and December 2002 in Cinta Kasih MaternityHospital. The inclusion criteria were fullterm baby, exclusivelybreastfed for 4 months, and informed consent from parents. Ba-bies with problems in organ or nerve that influenced the gastrointes-tinal tract were excluded. Stool frequency, consistency, and colorwere observed.Results The mean stool frequency per day were 3 times in the 1 stweek (95%CI 2.6;3.4), 2 times in the 2 nd week (95%CI 1.7;2.3),1.8 times in the 3 rd week (95%CI 1.5;2.1), and 1.5 times in the 4 thweek (95%CI 1.3;1.7). In the second and third month, it was 1.4times a day and the fourth month, 1.2 times a day. The consis-tency of meconium was soft in the first four days. After that, 18% ofbabies had watery stool, which increased to 30% on day 15-113.In the last week of the fourth month, all babies had soft stool. Meco-nium was black and lasted for 1-3 days. On the fourth day, thestool became yellow. On day 5-14, 6% of babies had green stool,which increased to 12% on day 15-120.Conclusion The first week of the first month was the week whenthe stool frequency was highest compared to the weeks or monthsafter. The consistency of meconium was soft. After it disappeared,most babies had soft stool. Eighteen up to 30% percent of babieshad watery stool. Regarding the color, meconium was black andstayed for 1-3 days. After that, most babies had yellow stool and 6-12% had green stool